2021
DOI: 10.1016/j.jemep.2021.100661
|View full text |Cite
|
Sign up to set email alerts
|

Moral injury and the COVID-19 pandemic: A philosophical viewpoint

Abstract: Introduction: Much has changed in healthcare during the coronavirus disease (COVID)-19 pandemic. Medicine, a profession of traditional principles and virtues, has faced unprecedented challenges in the light of scarce and unequal distribution of ventilators, testing, and personal protective equipment. Healthcare workers have been- and are increasingly likely to be- forced into situations that require difficult decision making under life-and-death conditions. Concepts of “medical necessity” and “maximum benefit”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…As above, we would argue that the frequent reliance on ad-hoc appeals for compassionate exemptions undermines just approaches to decision-making through making these instances seem an inappropriately exceptional (rather than expected) aspect of care. This case-by-case approach could also expose healthcare providers, tasked with deciding exemptions, to risk of moral injury due to their perception of a difference between their personal ethics and those of the prevailing institution (Akram 2021).…”
Section: Community Interests and Personal Autonomymentioning
confidence: 99%
“…As above, we would argue that the frequent reliance on ad-hoc appeals for compassionate exemptions undermines just approaches to decision-making through making these instances seem an inappropriately exceptional (rather than expected) aspect of care. This case-by-case approach could also expose healthcare providers, tasked with deciding exemptions, to risk of moral injury due to their perception of a difference between their personal ethics and those of the prevailing institution (Akram 2021).…”
Section: Community Interests and Personal Autonomymentioning
confidence: 99%
“…In the sense of contextual behaviors, Borges et al [ 65 ] stated that the COVID-19 pandemic brought into light many moral dilemmas. Akram [ 66 ] reported that the U.S. healthcare system adopted utilitarian policies to deal with moral injuries during the COVID-19 pandemic outbreak. Liang et al [ 67 ] studied and revealed respondents’ depressive behaviors and moral collapse from China’s Hubei province during the pandemic outbreak.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…Alarming prevalence of depression and anxiety have for example been reported worldwide ( da Silva and Neto, 2021 ; Lai et al, 2020 ; Sahebi et al, 2021 ; Wang et al, 2020 ). A less documented yet severe and preoccupying mental health consequence of the pandemic is the increased risk of moral injury (MI) in these workers (F. Akram, 2021a , Akram, 2021b ; Litam and Balkin, 2021 ; Shale, 2020 ). MI can arise from having to deal with the risk of being infected and infecting those close to them.…”
Section: Introductionmentioning
confidence: 99%